2009
DOI: 10.1007/s10735-009-9226-1
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 9 expression and its localization in normal skeletal myofiber

Abstract: The examination was performed whether aquaporin (AQP) 9 is expressed in normal skeletal muscle at mRNA and protein levels. Gel electrophoresis of the reverse transcription-polymerase chain reaction (RT-PCR) product of total RNA samples of human normal muscles by oligonucleotide primers for human AQP9 showed a band of 221 basepairs, which corresponded to the basepair length between two primers of AQP9. The nucleotide sequence of RT-PCR product coincided with that of human AQP9. Immunoblot analysis revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…The discrepant expression of AQP7 in the ob/ob mouse skeletal muscle and the adipose tissue of human diet induced obese subjects may be explained by the action of leptin which downregulates AQP7. The present studies confirmed our previous study [14] that the AQP9 was also expressed on the surface membrane of murine skeletal myofibers, especially in type 2 myofibers, although the expression level was not significantly different in the skeletal muscles between obese ob/ob mice and wild mice. Although AQP is suggested to be regulated by leptin through the phosphatidylinositol 3-kinase/Akt/mammalian target of rapamycin pathway in visceral adipocytes and hepatocytes [28], AQP7 may be more influenced by this pathway than AQP9 in the skeletal muscle.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The discrepant expression of AQP7 in the ob/ob mouse skeletal muscle and the adipose tissue of human diet induced obese subjects may be explained by the action of leptin which downregulates AQP7. The present studies confirmed our previous study [14] that the AQP9 was also expressed on the surface membrane of murine skeletal myofibers, especially in type 2 myofibers, although the expression level was not significantly different in the skeletal muscles between obese ob/ob mice and wild mice. Although AQP is suggested to be regulated by leptin through the phosphatidylinositol 3-kinase/Akt/mammalian target of rapamycin pathway in visceral adipocytes and hepatocytes [28], AQP7 may be more influenced by this pathway than AQP9 in the skeletal muscle.…”
Section: Discussionsupporting
confidence: 92%
“…General procedures for peptide syntheses and antibody production were similar to those described previously [14, 39]. Briefly, the peptide (MVQASGHRRSTRGSK-C) of the N-terminal end of the cytoplasmic domain in the human AQP7 molecule (Entrez NM001170) and the peptide (KAEQSEDKPEKYE-C) of the C-terminal end of the cytoplasmic domain in the human AQP9 molecule (Entrez NM020980) were synthesized and the extra cysteine was added to the C-terminus of AQP7 and AQP9 molecules.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previously described general procedures were used for peptide syntheses and antibody production [16,17]. Briefly, the peptide (MVQASGHRRSTRGSK-C) of the N-terminal end of the cytoplasmic domain in the human AQP7 molecule (Entrez NM001170) and the peptide (KAEQSEDKPEKYE-C) of the C-terminal end of the cytoplasmic domain in the human AQP9 molecule (Entrez NM020980) were respectively synthesized and the extra cysteine was added to the C-terminus of AQP7 and AQP9 molecules.…”
Section: Peptide Synthesis and Antibody Productionmentioning
confidence: 99%
“…In these original reports, AQP9 mRNA expression was found in a few tissues, most notably liver and leukocytes in humans (Ishibashi et al 1998;Tsukaguchi et al 1999), as well as liver and immature sperm in mice (Tsukaguchi et al 1998). Since then, AQP9 immunoreactivity has been found in many tissues, including rat and human epididymis (Elkjaer et al 2000;Pastor-Soler et al 2001), various cell types of rodent and primate brain (Elkjaer et al 2000;Badaut et al 2001;Badaut et al 2004;Amiry-Moghaddam et al 2005;Arcienega et al 2010), mouse spinal cord (Oshio et al 2004), human chorioamnion and placenta (Damiano et al 2001;Wang et al 2004), mouse and human inner ear (Huang et al 2002;Degerman et al 2011), mouse and human small intestine (Okada et al 2003), rat and human prostate (Wang et al 2008;Hwang et al 2012), human skeletal muscle (Inoue et al 2009), urothelium (Rubenwolf et al 2009), rat and porcine oviduct (Skowronski et al 2009), human adipose tissue (Rodriguez et al 2011), human retina (Tran et al 2013;Yang et al 2013), and mouse and human skin (Sugiyama et al 2014). …”
Section: Introductionmentioning
confidence: 99%